Relationship between haemoglobin and glucose in type 1 experimental diabetes. (June 2019) - Olvera, L I; Villanueva, G C; Cruz, A; Sanchez, N; Olvera, S J; Alvarado, M L
Abstract: 400 million people suffer diabetes around the world. It is the second cause of death in Mexico. The problem is that glucose control is difficult (mainly because of the poor treatment adherence) and the current biomarkers are not efficient enough for the early detection of diabetic complications (before symptoms are present). The goal of the present study was to use the technique called photoacoustic spectroscopy on blood samples obtained from diabetic male Wistar rats, to detect the optical absorption spectra related to haemoglobin. We assume that such spectra modifications are related to toxic heme, a product of haemoglobin, that could be associated with hyperglycaemia as well as the presence of diabetic complications. We postulate that changes on spectra of blood samples taken after 1 to 10 weeks of diabetes are related to the evolution of diabetes. It is necessary to analyse samples from diabetic animals at longer times, diabetes longer than 10 weeks, to find out if those changes have any relation with complications. We conclude that photoacoustic spectroscopy of haemoglobin could be used to assess the evolution of diabetes.